An educational intervention about the classification of penicillin allergies: effect on the appropriate choice of antibiotic therapy in pregnant women. (February 2020) - Thellier, C.; Subtil, D.; Pelletier de Chambure, D.; Grandbastien, B.; Catteau, C.; Beaugendre, A.; Poitrenaud, D.; Prevotat, A.; Richart, P.; Faure, K.; Le Guern, R.
Highlights: Classification of penicillin allergy symptoms is important during pregnancy. Educational interventions increase application of a penicillin allergy classification. Educational interventions improve appropriateness of antibiotic prescription. Abstract: Background: Most pregnant women who self-report penicillin allergy are not truly penicillin-allergic and this misunderstanding often leads to administration of inappropriate antibiotic therapy. Decision algorithms have been developed to guide antibiotic selection but major discrepancies have been reported between guidelines and clinical practice. We aimed to optimize the prescription of antibiotics for pregnant women who self-reported penicillin allergy, using an educational intervention about the classification of penicillin allergies that targeted gynecologists, anesthesiologists and midwives. Methods: This quasi-experimental study assessed the effect of an educational intervention about the classification of penicillin allergy. For six months, a combination of two strategies was used, namely dissemination of printed educational materials and group education. The principal study endpoint was the appropriateness of the antibiotic therapy, defined in advance for each level of allergic risk. Results: The pre-intervention phase included 903 women; one year after its conclusion, the post-intervention phase began and included 892 women. The prevalence of self-reported penicillin allergy was stable over the two periods (6.8% before vs 5.4% after, P =0.24). The clinical classification of penicillin allergies was more often used after the educational intervention (68% vs 100%, P <0.001). The appropriateness of the antibiotic therapy prescribed to self-reported penicillin allergic-women increased significantly between the two periods, from 5/29 (17.2%) to 18/27 (66.7%, P <0.001). Conclusion: An educational intervention about penicillin allergy classification was associated with an improvement in the choice of appropriate antibiotic therapy among women who had reported penicillin allergy.